Emigration and Feminization in Nepalese Agriculture: Implications for Food Security - Pandey, A.; Tripathi, K.; Devkota, S. (Journal of Agriculture and Environment, 2021)
Nepalese labor industry of agriculture sector is dominated by female and has direct and indirect effect on food security. This paper has attempted to find and analyze consequences of male emigration and feminization in agriculture, and implication on food security. The study revealed foreign employment as major reason for international migration of Nepalese people. Higher male emigration 91.3% with large remittance inflow has ensured food secure condition in short run but there is long run food insecurity threats due to lower domestic production and higher investment on consumption. Further extra work burden in female due to absence of active male labor and limited agriculture knowledge and skills in agri-business has resulted land abandonment and underutilization of agricultural resources. The study suggested to develop female friendly agricultural practices, investment on productive enterprises and attract youth and female in agriculture to ensure sustainable food security